Evolution of provenance in the NE Atlantic rift: The Early-Middle Jurassic succession in the Heidrun Field, Halten Terrace, offshore Mid-Norway - Morton, Andrew; Hallsworth, Claire; Strogen, Dominic; Whitham, Andrew; Fanning, Mark (Marine and Petroleum Geology, 2009)
An integrated provenance study using provenance-sensitive heavy mineral ratios, mineral chemistry and U/Pb dating of detrital zircons has revealed significant changes in sediment provenance during deposition of the Early to Middle Jurassic succession in the Heidrun Field, offshore Mid-Norway. The variations result from the interplay of two source regions, one of which was located on the Norwegian landmass and the other on the conjugate East Greenland margin. Sediment sourced from central East Greenland is distinguished by high garnet:zircon, high rutile:zircon, low chrome spinel:zircon, garnet assemblages rich in low-Ca, high-Mg varieties, and zircon populations that include an Archean group, a diverse range of Early-Middle Proterozoic grains, and an Early Paleozoic group. These features indicate derivation from a high-grade (granulite facies) metasedimentary terrain together with Archean basement and Early Paleozoic granitoids. Norwegian-sourced sandstones differ by having lower garnet:zircon and rutile:zircon, variable chrome spinel:zircon, garnet assemblages scarce in low-Ca, high-Mg varieties, and zircon populations that lack an Archean group. Derivation from the Caledonian Nappe Domain, comprising metasediments (predominantly at amphibolite facies), ophiolites and Early Paleozoic granitoids, is indicated. Initially, during deposition of the non-marine lower part of the Åre Formation (Hettangian-Sinemurian), sediment was fed from the west, but in the upper (tidally influenced) part of the Åre Formation (Sinemurian-Pliensbachian), Norwegian-sourced material appears. Greenland-derived material disappears in the subsequent Tilje Formation (Pliensbachian), with the Tilje and subsequent Ror and Ile Formations (Toarcian-Aalenian) being predominantly sourced from the east. The regional regression at the base of the Garn Formation (Bajocian) was accompanied by a switch in provenance, with Greenland-derived material replacing sediment sourced from Norway. Variations in mineralogy offer a framework for correlation on both local and sub-regional scales.